DEPICTION OF COMMON ENEMIES IN RELIGIOUS SPEECH: The Role of the Rhetoric of Identification and Purification in Indonesian Religious Conflicts - Suwarno, Peter (IAIN Walisongo Semarang, 2013)
AbstractThe role of common enemies in speech on religious issues have contributed toreligious tension, conflict and even violence in Indonesia. It will select the mostrepresentative and most frequently used key terms from religiously related speechesand other texts containing the portrayal of common enemies. Using Burkeâs theoriesof identification, this paper will explain the important roles of common enemies ingroup unity and in achieving certain objectives.***Peran musuh bersama dalam ceramah-ceramah agama telah memberikan kontribusiuntuk timbulnya tekanan, konflik, dan kekerasan di Indonesia. Bahan yangdigunakan dalam penelitian ini adalah istilah-istilah kunci yang sering digunakandalam ceramah maupun teks yang menggambarkan musuh bersama. Denganmenggunakan teori identifikasi dari Burke, tulisan ini akan menjelaskan peranpenting musuh bersama dalam kesatuan kelompok dan dalam rangka mencapaitujuan tertentu.Keywords: common enemy, religious speech, tense, conflict, violence